2002
DOI: 10.1007/bf02723216
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of asthma in India

Abstract: Allergic respiratory disorders, in particular asthma are increasing in prevalence, which is a global phenomenon. Even though genetic predisposition is one of the factors in children for the increased prevalence - urbanisation, air pollution and environmental tobacco smoke contribute more significantly. Our hospital based study on 20,000 children under the age of 18 years from 1979,1984,1989,1994 and 1999 in the city of Bangalore showed a prevalence of 9%,10.5%,18.5%, 24.5% and 29.5% respectively. The increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
104
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 7 publications
5
104
2
Order By: Relevance
“…However, the incidence of LRTI in present study was significantly lower when compared with the findings of Paramesh et al who reported the incidence of 12.85% in his study. 5 The reason can be explained by not including children <1 month and >12 years of age in the study. Incidence of RTI in an area is dependable upon multiple factors like season of the study, climatic factors of the region and cultural and traditional factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of LRTI in present study was significantly lower when compared with the findings of Paramesh et al who reported the incidence of 12.85% in his study. 5 The reason can be explained by not including children <1 month and >12 years of age in the study. Incidence of RTI in an area is dependable upon multiple factors like season of the study, climatic factors of the region and cultural and traditional factors.…”
Section: Discussionmentioning
confidence: 99%
“…A study from south Karnataka among rural children aged 6-15 years reported a prevalence of 10.5% 11 . Another study from Bangalore revealed that the prevalence of asthma in children less than 18 years has increased steadily from 9% in 1979 to 29.5% in 1999 5 . In Tamil Nadu, data from Chennai published in 2002 showed that the prevalence of diagnosed asthma was 5% in children below 12 years of age 6 .…”
Section: Discussionmentioning
confidence: 99%
“…There is also a wide variation (4% to 19%) in the prevalence of asthma in school going children reported from different geographical areas of India 4 . While in Bangalore it was 29.5%, the prevalence of diagnosed asthma in Tamil Nadu was only 5% 5,6 . Hence prevalence data from many more regions of India are needed.…”
Section: Introductionmentioning
confidence: 93%
“…[2][3][4][5] The steady rise in prevalence is correlated with demographic changes in city like increase in number of industries, increased density of population from migration of rural population and increased number of automobiles to commute resulting in air pollution. 5 Data on prevalence of asthma is now available from several countries. There is very limited data on asthma epidemiology from the developing countries including India.…”
Section: Introductionmentioning
confidence: 99%